SPEKULASI DALAM TRANSAKSI PASAR MODAL SYARIAH (POTENSI KEBERADAAN DAN SOLUSI PENANGANAN) - Ahmad Azizi; Muhammad Syarif Hidayatullah (Institut agama islam negeri Padangsidimpuan, 2021)
The research objective in this paper is to analyze the potential existence of speculation in transactions on the Islamic capital market and solutions in an effort to overcome the practice of speculation. Speculative activity that differentiates between Islamic investment and conventional investment is a problem in the contract concept. Gharar which is translated as speculation is equated with gambling because of the uncertainty of both parties (seller and buyer). Speculative activities that can damage liquidity and share prices make it a prohibited activity. The solution as an effort that can be done to reduce speculative activity in the Islamic capital market is to implement a minimum holding period policy, which is a policy of a minimum period for selling shares.